Pioneer violin virtuose in the early twentieth century : Maud Powell, Marie Hall, and Alma Moodie : a gendered re-evaluation /: Maud Powell, Marie Hall, and Alma Moodie : a gendered re-evaluation. (2019) - Goldberg, Tatjana
No abstract available